REPRESENTATION OF SYMBOLS IN “PARASITE” MOVIE - Tira Nur Fitria (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
Symbols as one of the primary media in the communication process which are directly capable of translating the thoughts and feelings of the communicator to the readers or audiences. In the Parasite movie, many symbols are hidden. This study investigates the representation of symbols in the Parasite movie. The method of this study was qualitative with a semiotic approach. The result analysis shows that several symbols found in the movie: Morse code, rain, underground (semi-basement), stone, smell, bunker (basement), and food can be seen in the “Parasite movie”. A Morse code symbol is a message. The code HELP being misinterpreted as HOLP cause the message not to be transmitted well. Rain as a symbol represents both the wealthy and the poor. Rain is a blessing to the wealthy but it is a curse to the poor, as it brings disasters (flooding). Underground is related to Kim's family home, who live in a cramped semi-basement space in a crowded complex. The stone's symbolism is linked to good fortune and prosperity. The viewing block (scholar stone) is spiritually idiosyncratic of good fortune and stable life. It symbolizes a sense of social status by smiles or implies a distinction between Kim's and Park's families about rich and poor people. Bunker (basement) is related to the hidden secret which is connected to the Park family's estate, only the former homeowner and housemaid know it. The final symbol is Ramdon, a food. It's a mixture of ramen and udon. This food has a symbiotic relationship due to the mixture of noodles and meat. As an act of showcasing the Park family's love of a "high-class" dish, an expensive steak was added on the cheap of an instant noodle.